University Students' Attitudes and Perceptions on Learning English with Mobile Apps - Mutalibovich, Sharipov Zabehullo; Margana; Gultom, Aryadi Manuel (Formosa Journal of Sustainable Research, 2024)
This study investigates university students' attitudes and perceptions toward using mobile applications for English language learning. Conducted at Universitas Negeri Yogyakarta with 43 master's students, the research employed a survey to assess various aspects of mobile app usage. Results indicate a generally positive view, with high engagement in listening and multimedia activities, underscoring the effectiveness of mobile apps in these areas. However, there are concerns about content accuracy and the need for improved support for writing skills. Students found mobile apps convenient and enjoyable, suggesting their significant potential to enhance language education. Recommendations include integrating mobile apps more systematically into curricula, focusing on features that support writing skills, and addressing concerns about information reliability. Future research should explore long-term impacts, effective integration strategies, and the role of specific app features in language development